Математичне моделювання пускових режимів електроприводу насоса підвищувача тиску води системи протипожежного водопостачання - Боднар, Григорій Йосипович; Шаповалов, Олег Валерійович (НТУ "ХПІ", 2010)
In the article rotined mathematical model of electromechanic pump of increase pressure water of the fire-prevention water which feeds from an autonomous source and results of researches system is resulted in the article.
Mathematical model of the starting modes of electromechanic pump of enlarger pressure water of the fireprevention water system
Keywords: ситуація надзвичайна; система електромеханічна; інвертор; напруга; вентиль; статор